Optomechanical entanglement between a movable mirror and a cavity field. - Vitali, D; Gigan, S; Ferreira, A; Böhm, H; Tombesi, P; Guerreiro, A; Vedral, V; Zeilinger, A; Aspelmeyer, M (2007)
We show how stationary entanglement between an optical cavity field mode and a macroscopic vibrating mirror can be generated by means of radiation pressure. We also show how the generated optomechanical entanglement can be quantified, and we suggest an experimental readout scheme to fully characterize the entangled state. Surprisingly, such optomechanical entanglement is shown to persist for environment temperatures above 20 K using state-of-the-art experimental parameters.